Research as Development Perspective - Samanidou, Victoria; Zachariadis, George (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue, "Research as a Development Perspective", is dedicated to data presented at the first Conference in Chemistry for Graduate/Postgraduate Students and PhD candidates at Aristotle University of Thessaloniki, which was the outcome of research conducted by young chemists in Northern Greece. The conference was organized by the Chemistry Department at Aristotle University of Thessaloniki, the Association of Greek Chemists-Division of Central and Western Macedonia, and the Association of Chemists in Northern Greece. The scope of this conference was to provide young chemists (but also last year's students) with the opportunity to be well prepared for their next career steps in an increasingly demanding job market. Moreover, they had the possibility of presenting their scientific results to a large audience, which strengthened their soft skills. Lastly, the active engagement of students in the organization of the conference enhanced their teamwork abilities, a highly valuable when developing professional maturity.